Oxygen in cluster headache - Dikmen, P. Yalinay; Aydinlar, E. Ilgaz; Kocaman, A. Sagduyu (SAGE PUBLICATIONS LTD, 2015)
International Headache Congress of the International-Headache-Society, Valencia, SPAIN, MAY 14-17, 2015